2013
DOI: 10.3109/17518423.2013.799243
|View full text |Cite
|
Sign up to set email alerts
|

Potential communicative acts in children with autism spectrum disorders

Abstract: Number of body movement types was not related to child ability, while number of gesture types was related to receptive and expressive language. Findings underscore the link between language and gesture, and offer support for an ecological systems perspective of language learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Coding behaviors in terms of their perceived communicative functions, based on the IPCA, has been used to identify the socio-communicative skills of children and adults with RTT mainly by interviewing caregivers and teachers (e.g., Didden et al, 2010; Sigafoos et al, 2000; Sigafoos, Woodyatt, Tucker, Roberts-Pennell, & Pittendreigh, 2000), ASD (Braddock et al, 2013; Keen, Woodyatt, & Sigafoos, 2001; Keen, Woodyatt, & Sigafoos, 2002; Keen, Woodyatt, & Sigafoos, 2005) and Angelman syndrome (Didden et al, 2009). This approach has also been applied to a more direct assessment, involving the retrospective analysis of videotapes (Bartl-Pokorny et al, 2013; Marschik, Bartl-Pokorny, et al, 2013; Marschik, Kaufmann, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Coding behaviors in terms of their perceived communicative functions, based on the IPCA, has been used to identify the socio-communicative skills of children and adults with RTT mainly by interviewing caregivers and teachers (e.g., Didden et al, 2010; Sigafoos et al, 2000; Sigafoos, Woodyatt, Tucker, Roberts-Pennell, & Pittendreigh, 2000), ASD (Braddock et al, 2013; Keen, Woodyatt, & Sigafoos, 2001; Keen, Woodyatt, & Sigafoos, 2002; Keen, Woodyatt, & Sigafoos, 2005) and Angelman syndrome (Didden et al, 2009). This approach has also been applied to a more direct assessment, involving the retrospective analysis of videotapes (Bartl-Pokorny et al, 2013; Marschik, Bartl-Pokorny, et al, 2013; Marschik, Kaufmann, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while the relation between early gesture use and later language is well established in typical development (Acredolo and Goodwyn 1988;Iverson and Goldin-Meadow 2005;Rowe and Goldin-Meadow 2009a;Rowe et al 2008), this relation has not been extensively studied in high-risk infants. In fact, previous findings have been mixed, with some studies showing positive, significant relations between early gesture and later vocabulary in children with ASD (Braddock et al 2015;Medeiros and Winsler 2014;Özçalışkan et al 2016), whereas others reported no significant relations between gesture and language in ASD (So et al 2015). Examining the relation between gesture and language may be useful in revealing whether such relation holds within the high-risk population and in predicting which infants will have subsequent language difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Three recent studies have examined whether and how cognitive and language abilities are correlated to gesture use in preschool children with ASDs. One study found that higher numbers of gesture types were positively associated with better language comprehension, language expression, and nonverbal thinking skills among 20- to 51-month-old children with ASDs (Braddock et al, 2013). Another study found that cognition and age explained only one-fourth of the variance in production of actions and gestures among 24- to 63-month-old children (Kjellmer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While Braddock et al (2013) and Kjellmer et al (2012) interviewed parents of children with ASDs or asked them to complete questionnaires, Mastrogiuseppe et al (2014) examined the relationship between language, cognitive abilities, and gestural production by collecting data through standardized assessments and naturalistic parent–child interactions. They found that the number of ideative gestures, which include iconic gestures and markers, was positively correlated with reasoning skills but negatively correlated with language skills among 30- to 66-month-old preschool children.…”
Section: Introductionmentioning
confidence: 99%